1963
DOI: 10.1063/1.1733582
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermodynamics of Solutions. IX. Critical Properties of Mixtures and the Equation of Benedict, Webb, and Rubin

Abstract: Values for the critical properties of gaseous mixtures derived from the equation of Benedict, Webb, and Rubin are not consistently better than those obtained from the equation of Redlich and Kwong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1965
1965
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…For a binary mixture, Redlich and coworkers [76][77] found that along the critical line, the limiting slopes at the critical points of two pure components can be explicitly derived from the critical criteria, as shown in Appendix B. They obtained fairly good results using classical EOS such as those by RedlichKwong and Benedict-Webb-Rubin.…”
mentioning
confidence: 99%
“…For a binary mixture, Redlich and coworkers [76][77] found that along the critical line, the limiting slopes at the critical points of two pure components can be explicitly derived from the critical criteria, as shown in Appendix B. They obtained fairly good results using classical EOS such as those by RedlichKwong and Benedict-Webb-Rubin.…”
mentioning
confidence: 99%
“…They may be very useful in representing data within a limited range of observation. Beyond this range great caution is advisable (Ackerman and Redlich, 1963).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors (1,14,17,19,21,22,34,36,44,45,63,64) have reported correlations of the critical temperature or critical pressure of mixtures but these, by and large, have been confined to a particular chemical c l a s s of substances (usually paraffins). Very little work has been reported on the correlation of critical volumes cf mixtures (22).…”
mentioning
confidence: 99%